The Teleological and Kalam Cosmological Arguments Revisited - Loke, Andrew (Palgrave Frontiers in Philosophy of Religion,, 2022)
'An innovative examination and defence of the cosmological and teleological arguments - accessible to the non-expert but pushing the debate into new territory with great originality and verve.' - T. J. Mawson, Oxford University, UK 'Andrew Loke's book provides an up-to-date assessment of the Teleological and Kalam Cosmological Arguments, including a thorough response to contemporary objections. It advances the discussion concerning the ultimate origin of the universe and makes a significant contribution to the field of philosophy of religion and the dialogue between science and religion.' - William Lane Craig, Biola University, USA 'This book provides an engaging guide to two important features of our universe - it seems to have had a beginning, and its ability to support life is remarkably rare - and their deeper implications. Up-to-date, wide-ranging and highly recommended.' - Luke Barnes, Western Sydney University, Australia A prominent issue in many contemporary philosophy of religion debates concerns whether the universe has a Designer. This book moves the discussion ahead in a significant way by devising an original deductive formulation of the Teleological Argument (TA) which demonstrates that the following are the only possible categories of hypotheses concerning fine-tuning and order: (i) chance, (ii) regularity, (iii) combinations of regularity and chance, (iv) uncaused, and (v) design. This book also demonstrates that there are essential features of each category such that, while the alternatives to design are unlikely, the Design Hypothesis is not, and that one can argue for design by exclusion without having to ﬁrst assign a prior probability for design. By combining the TA with the Kalam Cosmological Argument (KCA) which it defends against various objections, this book responds to the God-of-the-gaps objection by demonstrating that the conclusion of the KCA-TA is not based on gaps which can be filled by further scientific progress, but follows from deduction and exclusion. This is an open access book. Andrew Loke is Associate Professor, Department of Religion and Philosophy, Hong Kong Baptist University, China.